A meta-analysis of the incidence and fate of contralateral vesicoureteral reflux in unilateral multicystic dysplastic kidney. Issue 1 (February 2019) - Erlich, T.; Lipsky, A.M.; Braga, L.H.
Summary: Introduction: Multicystic dysplastic kidney (MCDK) is the most common type of renal cystic disease. It is associated with urinary tract abnormalities in the contralateral kidney in up to 30% of cases, most commonly vesicoureteral reflux (VUR). Objectives: The objective of this study was to describe the incidence and selected issues in management and evolution for each VUR grade in the contralateral kidney of patients with unilateral MCDK, in order to strengthen the scientific basis regarding the need for voiding cystourethrography (VCUG) screening. Methods: A comprehensive search of standard and gray literature was performed. Full-text screening, data abstraction, and quality appraisal were conducted in duplicates. Included studies reported a primary diagnosis of unilateral MCDK with contralateral VUR determined by VCUG. Articles had to include a distribution of VUR grade to meet the eligibility criteria. Results: From 698 retrieved articles, 37 studies enrolling 2057 patients were analyzed. Of the patients, 80% were male; 50% had left unilateral MCDK; and 87% were diagnosed prenatally. A total of 1800 patients had VCUG, of whom 303 had VUR (weighted proportion: 17%; 95% confidence interval [CI]: 14–20%). Weighted proportions of VUR were 9%, 7%, and 17% for grades I–II, III–V, and I–V, respectively. Of the patients, 99% (95% CI: 97–100%) were on continuous antibiotic prophylaxis (CAP) and 18% (95% CI: 8–37%) had urinary tract infections (UTIs), with a higher rate of UTIs (23% vs 10%) in patients with dilating (grades III–V) VUR, over a mean follow-up of 40 months. In patients with dilating VUR, reflux resolved or downgraded to grade I in 52% (95% CI: 37–67%) of patients, and 32% (95% CI: 19–49%) had surgical correction of VUR. Conclusions: Among patients with unilateral MCDK, 17% have VUR in the contralateral kidney, 41% of which is dilating VUR. Of the cases with dilating VUR, half will resolve or downgrade to grade I during follow-up; 23% will develop a UTI despite CAP; and one-third will undergo ureteral re-implantation. While many physicians may thus choose to forego routine VCUG screening of the single functional kidney, shared decision-making with the patient's caregivers is currently recommended, where the risks and benefits of the different approaches can be discussed. The data from this analysis can help inform the discussions.Table for extended summary – Summary of primary outcomes. VUR grade Number of studies Number of VUR patients Pooled proportion (95% CI) Heterogeneity Cochran Q P-value I 2 (95% CI) I 35 35 2% (1-3) 18.5 0.99 44% II 35 102 6% (5-8) 41.4 0.18 43% III 36 79 4% (3-6) 33.5 0.54 43% IV 37 32 2% (1-3) 19.2 0.99 0% V 37 18 1% (0-2) 20.7 0.98 55% I-II 35 137 9% (7-11) 48 0.06 45% III-V 36 127 7% (6-9) 45.8 0.1 36% Total (I-V) 37 303 17% (14-20) 115.7 <0.01 69% Bold values represent groups of VUR grades.